2015
DOI: 10.1038/srep10066
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus replication and sex-determining region Y box 4 production are tightly controlled by a novel positive feedback mechanism

Abstract: Hepatitis B virus (HBV) infection is a major cause of liver diseases. However, the mechanisms underlying HBV infection and pathogenesis remain largely unknown. The sex-determining region Y box 4 (Sox4) is a transcriptional factor, which preferentially regulates the development of various organs, tissues, and cancers. But, the role of Sox4 in viral infection and pathogenesis has not been elucidated. Here, we demonstrated that Sox4 is up-regulated by HBV, and revealed the mechanism by which HBV regulates Sox4 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…This region contains three putative binding sites for the transcription factor YY1 [36]. Dual luciferase reporter assays in HEK 293 T cells, with constitutive expression of CASC15 , caused increased SOX4 promoter activity (Additional file 7: Figure S5d).…”
Section: Resultsmentioning
confidence: 99%
“…This region contains three putative binding sites for the transcription factor YY1 [36]. Dual luciferase reporter assays in HEK 293 T cells, with constitutive expression of CASC15 , caused increased SOX4 promoter activity (Additional file 7: Figure S5d).…”
Section: Resultsmentioning
confidence: 99%
“…The sex-determining region Y box 4 (Sox4) is a TF that preferentially regulates the development of various organs, tissues, and cancers. In a cDNA microarray study by Shang et al, 8 Sox4 expression was found to be closely related to HBV replication network. The investigators further showed that HBV stimulates upregulated expression of Sox4 through the indispensable YY1 protein, which is itself upregulated by HBV through MAPK signaling and binds to the Sox4 promoter to activate Sox4 transcriptional activity.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Studies have indicated that YY1 regulates other signaling pathways that facilitate HBV replication. Shang et al discovered that YY1 activates the sex-determining region Y box 4 protein in HepG2 cells with opposing results in control cells, suggesting a role in HBV replication [185].…”
Section: Yin Yangmentioning
confidence: 99%